Curriculum Reform in Brunei Darussalam’s Education System in Realizing Brunei Vision 2035 - Setyawan, Roby; Helmiati; Muhammad Nazir (The Future of Education Journal, 2025)
Curriculum reform in Brunei Darussalam is a strategic step in supporting the national vision, Brunei Vision 2035, which aims to build a well-educated, highly skilled society with the highest standard of living. This transformation is reflected through the implementation of the 21st Century National Education System (SPN21), which focuses on competency development, technology integration, character education, and the application of a bilingual curriculum. The reform encompasses not only primary and secondary education levels but also vocational and higher education, with active involvement from both the business sector and the government. Through this approach, Brunei strives to produce a generation that excels academically and is well-equipped to face global challenges with competence and integrity.